TFF1 and TFF3 mRNAs Are Higher in Blood from Breast Cancer Patients with Metastatic Disease than Those without. (7th June 2018) - Elnagdy, Marwa H.; Farouk, Omar; Seleem, Amal K.; Nada, Hoda A.
Abstract : Introduction . Breast cancer metastasis occurs when tumor cells dissociate from the primary tumor and migrate to distant organs through the peripheral bloodstream or lymphatic drainage. Circulating tumor cells (CTCs) originate from primary sites or metastases and circulate in the patients' bloodstream. Molecular assays for the detection and molecular characterization of CTCs can serve as a liquid biopsy and can represent an alternative to invasive biopsies as a source of tumor tissue in the metastatic patients. Patients and Methods . We analyzed the presence of CTCs in the peripheral blood of 50 breast cancer patients by quantitative real-time reverse transcriptase polymerase chain reaction (RT-qPCR) to detect trefoil factor family ( TFF ) 1 and 3 genes. Results . We found significant difference in the level of both TFF1 and TFF3 mRNA in the blood of nonmetastatic versus metastatic breast cancer patients (p= 0.001 and p= 0.038, respectively). TFF1 mRNA was detected at higher levels in 34.6% of metastatic breast cancer patients as compared to 0% of nonmetastatic (p= 0.002). As regards TFF3 mRNA, it was detected at higher levels in 46.2% of metastatic breast cancer patients as compared to 4% of nonmetastatic (p= 0.026). Moreover, we found that the high level of both TFF1 and TFF3 mRNA was related to estrogen status of the patients. The detection of high level of TFF1 mRNA in CTCs was associated with bone metastases (77.8%), while that of TFF3 was related to lymph node involvement (75%) and lung metastases (68.8%). Conclusion . The combined measurement of both TFF1 and TFF3 mRNA level for differentiation of metastatic from nonmetastatic breast cancer gave 57.69% sensitivity and 83.3% specificity.